Factors Enhancing Electronic-Citizen Satisfaction in The Context of Malaysian Electronic Government - Mahmoudi, Arezou (2010)
This study was done to display the updated distributed survey in 2010. The important elements of improving services are the points of view, participation, feedback and satisfaction of people who use these services. Therefore the author attempted to measure citizen satisfaction in different dimensions and factors.